Cup Feeding as a Supplemental, Alternative Feeding Method for Preterm Breastfed Infants: An Integrative Review. - Penny, Frances; Judge, Michelle; Brownell, Elizabeth; McGrath, Jacqueline M (Maternal and child health journal, 2018)
Background The benefits of human milk for the preterm infant are well established. Preterm infants have lower breastfeeding rates and often face breastfeeding challenges. It is important that feeding practices for preterm infants optimize their chances of breastfeeding. Objective The purpose of this integrated review is to synthesize and critically analyze research related to the safety and efficacy of cup feeding as an alternative, supplemental feeding method for breastfed infants. Data Sources The electronic data bases of PubMed, CINAHL and were used to identify studies published in English from 1998- 2017. Design Using inclusion and exclusion criteria, 27 articles were initially assessed. After further screening 19 articles were included in the full review and of these 5 more were excluded. Lastly, an in-depth review of these 14 studies resulted in 2 more exclusions, for a total of 12 studies that met full inclusion and exclusion criteria. Review Methods Studies were examined for information on safety and efficacy of cup feeding as an alternative, supplemental feeding method for preterm breastfed infants. Studies were grouped into categories of outcomes that included (a) safety and physiologic properties; (b) breastfeeding outcomes. Results Use of cup feeding resulted in more stable heart rate and oxygen saturation than bottle feeding with similar weight gain. Additionally, breastfeeding rates were higher at discharge with continued higher rates at 3 and 6 months post-discharge for cup fed infants. Conclusions Premature infants face more breastfeeding obstacles than term infants. The potential for cup feeding as an alternative to bottle-feeding for breast fed preterm infants is positively supported by these results It is fundamentally important for NICU professionals to establish a protocol, education and training for the potential use of this feeding method for this vulnerable population.
13 citations (Crossref) [2023-10-31] Place: United States Penny, Frances. Department of Nursing, Southern Connecticut State University, 501 Crescent Street, New Haven, CT, 06515, USA. Pennyf1@southernct.edu. Penny, Frances. School of Nursing, University of Connecticut, Storrs, CT, USA. Pennyf1@southernct.edu. Judge, Michelle. School of Nursing, University of Connecticut, Storrs, CT, USA. Brownell, Elizabeth. Connecticut Children's Medical Center, Hartford, CT, USA. Brownell, Elizabeth. School of Medicine, University of Connecticut, Farmington, CT, USA. McGrath, Jacqueline M. School of Nursing, University of Connecticut, Storrs, CT, USA. McGrath, Jacqueline M. Connecticut Children's Medical Center, Hartford, CT, USA.
Keywords: *Bottle Feeding; *Breast Feeding/mt [Methods]; *Cooking and Eating Utensils; *Enteral Nutrition/mt [Methods]; *Feeding Methods; *Infant; Premature/ph [Physiology]; Alternative feeding; Bottle Feeding; Breast Feeding; Breastfeeding; Cooking and Eating Utensils; Cup feeding; Enteral Nutrition; Enteral Nutrition/is [Instrumentation]; Feeding Methods; Female; Humans; Infant; Newborn; Infant; Premature; Infants; Male; Preterm; bottle feeding; breast feeding; dept.nur; devices; enteric feeding; female; food intake; human; kitchen; male; newborn; peer-reviewed; physiology; prematurity; procedures